Relative Risk Estimation of Tuberculosis with Standardized Morbidity Ratio in Malaysia - Mohd Diah, Ijlal; Aziz, Nazrina; Ahmad, Nazihah (Research India Publications, 2016)
TB is a widespread disease which is one of several factors that cause millions of death worldwide. The numbers of TB cases reported keep on increasing from year to year.Moreover, this type of disease can become epidemic and also pandemic if it is not controlled.Disease mapping can be used in controlling and as the prevention strategies for a disease as it can give clear picture of the risk areas.It relies on the modeling used to estimate the relative risk to get an accurate disease map.The purpose of this study is to estimate relative risk for TB disease transmission using the most common statistic used in disease mapping that is Standardized Morbidity Ratio (SMR).This relative risk estimation is applied to TB data in Malaysia.Then this value will be displayed in a map to represent TB risk areas.Perlis shows the lowest risk areas of contracting TB while Sabah & Labuan has the highest risk area.